2011
DOI: 10.1111/j.1600-0838.2011.01417.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional and muscle morphometric effects of ACL reconstruction. A prospective CT study with 1 year follow‐up

Abstract: Computed tomography (CT) was used to explore if changes in muscle cross-sectional area and quality after anterior cruciate ligament (ACL) injury and reconstruction would be related to knee function. Fourteen females and 23 males (16-54 years) underwent clinical tests, subjective questionnaires, and CT 1 week before and 1 year after ACL surgery with semitendinosus-gracilis (STG) graft and rehabilitation. Postoperatively, knee laxity was decreased and functional knee measures and subjective patient scores improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
2
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(84 citation statements)
references
References 48 publications
4
75
2
3
Order By: Relevance
“…In a previous study we have shown that females had worse subjective as well as functional hop test outcomes one year after surgery, and some lack of muscular development after surgery compared to males [15]. The present study confirms the lower subjective score ratings for females (KoSp subscale score).…”
Section: Outcome Twelve Months After Surgerysupporting
confidence: 94%
See 4 more Smart Citations
“…In a previous study we have shown that females had worse subjective as well as functional hop test outcomes one year after surgery, and some lack of muscular development after surgery compared to males [15]. The present study confirms the lower subjective score ratings for females (KoSp subscale score).…”
Section: Outcome Twelve Months After Surgerysupporting
confidence: 94%
“…Post-operative bracing neither prevented joint effusion measured at three-months post-operatively nor one-year functional and subjective outcome parameters. The results from the present study confirm our previous study findings regarding clinical, functional, subjective and muscle morphologic parameters [15]. We may thus conclude that post-operative bracing has no role after ACLR with a ST/G graft.…”
Section: Post-operative Bracingsupporting
confidence: 93%
See 3 more Smart Citations